Discovery of a novel anticancer agent with both anti-topoisomerase I and II activities in hepatocellular carcinoma SK-Hep-1 cells in vitro and in vivo: Cinnamomum verum component 2-methoxycinnamaldehyde - Perng DS; Tsai YH; Cherng J; Wang JS; Chou KS; Shih CW; Cherng JM (Dove Medical Press, 2016)
Daw-Shyong Perng,1 Yu-Hsin Tsai,2 Jonathan Cherng,3 Jeng-Shing Wang,4 Kuo-Shen Chou,5 Chia-Wen Shih,6 Jaw-Ming Cherng7 1Department of Gastroenterology, E-Da Hospital, I-Shou University, Kaohsiung, Taiwan, Republic of China; 2Sierra College, Rocklin, CA, USA; 3Faculty of Medicine, Medical University of Lublin, Lublin, Poland; 4Department of Internal Medicine, Antai Tian-Sheng Memorial Hospital, Pingtung, 5Department of Family Medicine, Saint Mary’s Hospital Luodong, 6Department of Pathology, Lotung Poh-Ai Hospital, 7Department of Internal Medicine, Saint Mary’s Hospital Luodong, Yilan, Taiwan, Republic of China Abstract: Cinnamomum verum is used to make the spice cinnamon and has been used as a traditional Chinese herbal medicine for various applications. We evaluated the anticancer effect of 2-methoxycinnamaldehyde (2-MCA), a constituent of the bark of the plant, and its underlying molecular biomarkers associated with carcinogenesis in human hepatocellular carcinoma SK-Hep-1 cell line. The results show that 2-MCA suppressed proliferation and induced apoptosis as indicated by mitochondrial membrane potential loss, activation of caspase-3 and caspase-9, increase in the DNA content in sub-G1, and morphological characteristics of apoptosis, including blebbing of plasma membrane, nuclear condensation, fragmentation, apoptotic body formation, and long comet tail. In addition, 2-MCA also induced lysosomal vacuolation with increased volume of acidic compartments, suppressions of nuclear transcription factors NF-κB, cyclooxygenase-2, prostaglandin E2 (PGE2), and both topoisomerase I and II activities in a dose-dependent manner. Further study reveals the growth-inhibitory effect of 2-MCA was also evident in a nude mice model. Taken together, the data suggest that the growth-inhibitory effect of 2-MCA against SK-Hep-1 cells is accompanied by downregulations of NF-κB-binding activity, inflammatory responses involving cyclooxygenase-2 and PGE2, and proliferative control involving apoptosis, both topoisomerase I and II activities, together with an upregulation of lysosomal vacuolation and volume of acidic compartments. Similar effects (including all of the above-mentioned effects) were found in other tested cell lines, including human hepatocellular carcinoma Hep 3B, lung adenocarcinoma A549, squamous cell carcinoma NCI-H520, colorectal adenocarcinoma COLO 205, and T-lymphoblastic MOLT-3 (results not shown). Our data suggest that 2-MCA could be a potential agent for anticancer therapy. Keywords: 2-methoxycinnamaldehyde, anticancer, SK-Hep-1 cells, topoisomerase I, topoisomerase II